Associations between coping, thought control and psychological distress. (9th September 2016) - Ragan, Kathryn; Pugh, Lauren; Degnan, Amy; Berry, Katherine
Abstract: Ways of coping with stressful situations can be categorized as problem-focused, emotion-focused, and dysfunctional. Methods of controlling intrusive thoughts, which are frequently associated with psychological distress, have also been classified into different subgroups. This study assesses associations between methods of coping and thought control, and how these relate to distress. Sixty-eight participants were recruited from outpatient psychology services and completed measures of distress, coping, and thought control. Problem-focused coping strategies and both distraction and social thought-control strategies were associated with each other and with lower distress. Conversely, dysfunctional coping strategies and both worry and punishment thought-control strategies were associated with each other and with higher distress. Future research and the clinical implications are discussed.